EFFECTS OF TUBERCULOSIS INFECTION ON AGRICULTURAL PRODUCTIVITY IN OKPOKWU LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Abah, D.; Obekpa, H. O.; Okoliko, J. (Journal of Agripreneurship and Sustainable Development, 2020)
The study was carried out to determine the effect of tuberculosis infection on agricultural productivity in Okpokwu Local Government Area of Benue State, Nigeria. Data was collected for the study from primary source by the use of a well-structured questionnaire; the data was analyzed using descriptive statistics and regression analysis. The result shows that majority of the farmers infected with tuberculosis are males, married and have attain secondary education, majority also have farming as their major occupation. Majority of the farmers (64.7%) fell between the ages of 21-40, (58.8%) of the farmers have household size of 4-6 persons. All the respondents (100.0%) have experience cases of tuberculosis in their family which lowers productivity in the study area. Tuberculosis however has a negative impact on agricultural productivity. Duration of infection and cost of treatment were significant 1% and 5% levels of significance, respectively, showing that unit increase in these variables lead to decrease in productivity of farmers in the study area. It was, therefore, recommended that government should make clinics and hospitals available, affordable and accessible to farmers in the rural areas and also organize tuberculosis campaign programs like that of HIV to educate rural farmers on issues of tuberculosis how to prevent and control tuberculosis, and compensate infected farmers on their loss of time and resources.